Leading schools through and beyond the pandemic - Hardie, Suzy; Goode, Helen (Educator); Gurr, David (Lecturer in educational leadership) (International research on school leadership., 2024)
"Much of the literature has relied on others commenting on the work of educational leaders, rather than the voice of the leaders driving the commentary. There have been few studies attempting to capture principal voices within and between countries. The International School Leadership Development Network (ISLDN) was formed in 2009 and has had scholars from more than 20 countries involved (Barnett & Woods, 2021). In response to the pandemic, the ISLDN embarked on a study that analyzed the impact Covid-19 had on the school leaders and the way that they lead. The study captures a unique timeframe as the school leaders were still leading through the pandemic and adjusting to leadership after a global pandemic. We sought to investigate what impact a global pandemic had on principals and on their leadership practices during the pandemic. Through a series of questions we heard their stories: how they led their schools through the pandemic; what they had learned about themselves; how they had managed their wellbeing, what new practices they had implemented and, most importantly, what learnings they were taking forward. In this book we are using these cases to describe how principals not only led their schools during the pandemic, but what they are doing as we come out of the pandemic. The book includes the cases of 37 principals from seven countries, including many different states of the US. What makes this book different from many of the other publications about education and the pandemic is: 1. Principal voice is often missing from research and writing about the educational impact of the COVID pandemic. 2. The book draws upon empirical research conducted in 2022. It is reporting on principal case studies collected as part of the research of the International School Leadership Development Network. There are 37 principal cases from seven countries, and 25 writers. These cases have not been reported elsewhere and were collected especially for the book. 3. The cases are focused not only on how principals led their school through the pandemic, but how they are leading beyond the pandemic. A feature of the cases is reflection on enduring changes to education and the implications for future educational leadership 4. Whilst principals discuss their responses to the various mandates and pressures, and what worked well and what could have been done better, they also reflect on the support they gave others, and the support they got"--